Kajian Manajemen Sport Tracking di Desa Sambangan - Eka Budi Darmawan, Gede (Media Ilmu Keolahragaan Indonesia, 2012)
The aims of this research is to descrip of sport tracking management and to increase of sport tracking in Sambangan village. The benefit is to get profile scientific information how to increase management and sport tracking in sambangan Village. This research used decriptive, with collecting data used observation technique (to know and take track and location), interviewed (to get information from informan, management people, sadar wisata tanjung mekar member). The result are showed that group of Sadar wisata tanjung mekar in implentation of Ã‚Â sport management there are: 51,92% in Planning, 46,79% in organization, 49,57% in actuating, and 52,56% in evaluation. The totality of implementation management function are 50,21%. That is showed that in implementation of sport tracking un maksimum, so that is need how to increase sport tracking with reorginize with right target and empowering administration and member, the provision facility dan preparing human resaurce to develop.